Impact of Ovine Whey Protein Concentrates and Clarification By-Products on the Yield and Quality of Whey Cheese - Carlos D. Pereira (Food Technology and Biotechnology, 2007)
The effects of the addition of whey protein concentrates and clarification by-products obtained from ovine cheese whey and deproteinized whey (Sorelho) on the yield and quality of the whey cheese (Requeijão) have been evaluated. Whey protein concentrates were obtained by ultrafiltration of skimmed whey and Sorelho. The clarification by-products were obtained after the treatment of the skimmed whey and Sorelho by thermocalcic precipitation and microfiltration with two membranes (0.20 and 0.65 μm pore size). Next, the liophilization of the corresponding retentates was carried out. Each powder was added in three different mass ratios: 0.5, 1.0 and 1.5 %. The addition of the powders caused higher yields of the whey cheese – mainly the one with the additional whey powder – but it did not affect the strength of the products. The retention of water and other components of whey and milk in the whey cheese was influenced by the protein composition of the powders. In relation to colour parameters, the whey cheese manufactured with ultrafiltration and microfiltration retentate powders showed lower values of ligthness than the control whey cheese – mainly the whey cheese with 1.5 % of added powders. The microstructure constituted of small aggregates in the whey cheese manufactured with ultrafiltration and 0.20-μm microfiltration retentate powders and also by large, smooth structures in the other whey cheeses, especially in batches with added Sorelho powders.